Preoperative pain neuroscience education for shoulder surgery: A case series - Adriaan Louw (South African Journal of Physiotherapy, 2020)
Background: Central sensitisation, in addition to high levels of fear-avoidance and pain catastrophisation may exist in a subgroup of patients with shoulder pain. Pain neuroscience education (PNE) has been shown to positively influence sensitivity of the nervous system, as well as reduce fear and catastrophisation prior to lumbar and total knee surgery. To date, no study has examined the application of PNE prior to shoulder surgery.